The Role of Virtual Reality (VR) in Improving English Language Speaking Skills in Uzbekistan - Khamidova. H. Sh; Usmanova. G. T. (Development in Language Studies, 2025)
With the advancement of technology, Virtual Reality (VR) has emerged as a transformative tool in English language education, particularly in enhancing speaking skills. Traditional language learning methods often fail to provide an immersive, interactive, and anxiety-free environment for learners to practice speaking. However, VR offers a dynamic platform that mimics real-life communication, allowing learners to practice conversations in diverse settings without the fear of judgment. This study explores the role of VR in improving English-speaking proficiency, focusing on its impact on pronunciation, fluency, confidence, and engagement. The paper also highlights key challenges in the adoption of VR-based learning and suggests future directions for integrating this technology into language education.